Don’t Wake a Snake that Is Sleeping: An Anti-Xenophobia Education Campaign in Cape Town Townships (South Africa) - (:unkn) unknown (My University, 2021)
Since the end of apartheid in 1994, South Africa has attracted many African migrants fleeing conflict or poverty. Often scapegoated in a country where inequalities persist, they are regularly the target of attacks in the townships. The particularly violent attacks of 2008 encouraged NGOs providing services for migrants to organise awareness-raising activities on migration issues for township residents. To understand their approach, this article focuses on a working document—a worksheet—used by the Agency for Refugee Education, Skills Training and Advocacy (ARESTA) in its anti-xenophobia education campaign. The analysis focuses on the institutional vision of migration and xenophobia that this worksheet conveys, which ARESTA and its main donor, the UNHCR, both support. It also sheds light on the particular interpretation of the worksheet by an ARESTA employee during sessions in schools when he is assigned to address a teenage audience. For this employee, it is necessary to be able to talk about migration and xenophobia without “waking up a snake that is sleeping,” i.e. without arousing xenophobic sentiments that ARESTA aims to fight. Although he sometimes has to tinker with the “depoliticised political discourse” (as Bourdieu put it) of the UNHCR and ARESTA and adapt it to his objective and to his audience, he avoids sensitive issues and gets around difficulties by depoliticising the topic of migration and xenophobia. The universal arguments that he uses, which aim to be consensual at all costs, prevent the construction of a “we” that would challenge the citizen/foreigner distinction at the root of xenophobia.
Keywords: African Research